Comparative Analysis of Financial Performance in Sharia Banking and Conventional Banking - Agustyawati, Dwi; Rusdin, Rusdin (International Journal of Management Progress, 2022)
This study aims to determine the financial performance of Bank Muamalat and provide evidence of differences between financial performance comparisons between Bank Muamalat Rakyat and Bank Rakyat Indonesia (BRI). This type of research is a type of descriptive analysis. This type of descriptive research aims to determine the average value of each Islamic Commercial Bank and Conventional Bank and determine the composite rating of each Islamic Commercial Bank and Conventional Bank according to the RGEC system, so that a comparison is made. The sample for this research is Bank Muamalat Indonesia and its subsidiary Bank Rakyat Indonesia in 2019-2021. This study used two methods of collecting data from case studies and academics. The results of the study show that almost all NPF ratios at Bank Muamalat change every year. Based on the results of the 2019-2021 FNP calculation, Bank Muamalat has an average FNP of 5.19%, while Bank Rakyat Indonesia has an average NPL of 2.17%. Bank Muamalat's GCG self-assessment for the 2019-2021 period has an average GCG score. 1.57. In general, seen from the level of composition, the average at Bank Muamalat has a score of 2, which means that the implementation of GCG is good. The GCG value for Bank BRI in 2019 and 2021 is that it has an average of 2.00, meaning it is able to perform better than the industry average.